The Early Roman Canon Missae - Ratcliff, E. C. (The journal of ecclesiastical history, 1969)
In 1950 the late Professor Ratcliff published in the first two numbers of this Journal an article entitled ‘The Sanctus and the Pattern of the Early Anaphora’. In it he argued that the recitation of the Sanctus formed the climax and doxology of the primitive Eucharistic Prayer. At the end of the article he wrote, ‘Why, if the pattern of the ancient Anaphora ever conformed with the reconstruction proposed here, was the pattern abandoned? The surviving literature, and not least the historic liturgies, either supply the answers or offer evidence which suggests them. A consideration of the questions and answers, however, must be reserved for a future article’.